2022
DOI: 10.14393/bj-v38n0a2022-54228
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging test in the determination of safflower seeds vigor

Abstract: In assessing the quality of seed lots, the vigor tests are complementary to the germination test and they identify differences in the degree of deterioration of the lots. For safflower, there is little information regarding these tests. In this way, the intention of this study was to adapt the accelerated aging test methodology to assess the physiological potential of safflower seeds (Carthamus tinctorius). For this purpose, 12 seed lots were evaluated for thousand-seed weight, germination, first germination c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The principal component analysis of the soybean seed treatments was adequate, as the values of the principal components were similar to those found in studies evaluating soybean seed lots [ 28 ] and safflower vigor tests [ 29 , 30 ]. According to [ 31 ], a relatively small number of components were extracted (PC1 and PC2), with the ability to explain the highest variability in the original data.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The principal component analysis of the soybean seed treatments was adequate, as the values of the principal components were similar to those found in studies evaluating soybean seed lots [ 28 ] and safflower vigor tests [ 29 , 30 ]. According to [ 31 ], a relatively small number of components were extracted (PC1 and PC2), with the ability to explain the highest variability in the original data.…”
Section: Discussionsupporting
confidence: 64%
“…The multivariate data analysis methods allow a global study of these variables, evidencing the connections, similarities, or differences between them with the least possible loss of information [ 26 , 29 , 30 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced in this investigation, a decrease in germination rates following the AA test was observed across numerous plant species: wheat [18], rise [19], oilseed rape [20], soybean [21], and safflower [22]. Elevated temperatures and high relative humidity levels to which seeds are subjected during the AA test and CD test induce heightened seed moisture content and increase the activity of hydrolytic enzymes.…”
Section: Resultsmentioning
confidence: 55%
“…Barbosa et al (2011), when evaluating lettuce seeds by the accelerated aging method with saturated saline solution, found that the best exposure time to assess the potential of these seeds was 72 hours. Lopes et al (2010), also observed that the best period of exposure of okra seeds, using accelerated aging with saturated saline solution was 72 hours.…”
Section: Resultsmentioning
confidence: 89%
“…It was found that the water content of the seeds exposed to the saline solution (Table 5) showed lower values, after the aging periods in relation to those observed for the traditionally aged seeds. This indicates that the use of saline solution contributes to delay the absorption of water by the seeds in the accelerated aging test (Lopes et al 2010). Tunes et al (2012b) observed that in traditionally aged broccoli seeds, they reached higher water contents and with greater variations, when compared to aging with saline solution.…”
Section: Resultsmentioning
confidence: 99%